Pengaruh Pertumbuhan Ekonomi dan Rata-rata Lama Sekolah terhadap Tingkat Pengangguran Terbuka di Kabupaten Bantul - Desembriarto, Dionysius (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
Open unemployment is still a problem in almost all developing countries, including Indonesia in general and Bantul Regency in Yogyakarta in particular. The employment problem has social and economic dimensions and is multidimensional. The open unemployment rate in Bantul Regency has been fluctuating from year to year, which means that the potential problems of the open unemployment rate can still be experienced in the coming years. This study aims to analyze the variables that affect the open unemployment rate in Bantul Regency. The data used is secondary data sourced from the publications of BPS DIY Province and BPS Bantul Regency. The results of the study using a regression model found that economic growth had a negative and significant effect on the open unemployment rate, while the average length of schooling had no significant effect. The research recommendation is that increasing economic activity is important in reducing the unemployment rate. Economic development policies should be directed at the development of businesses or the private sector that operate by requiring a relatively high educated workforce in order to absorb more educated workers.